2019
DOI: 10.1055/s-0038-1677541
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between Cartilaginous and Bony Sulcus Angles for Patients with or without Patellofemoral Instability: A Systematic Review and Meta-Analysis

Abstract: The cartilaginous sulcus angle and bony sulcus angle have been widely used to evaluate trochlea dysplasia. The current review aims to evaluate (1) whether there is a difference in measurement for cartilaginous and bony sulcus angles, (2) whether both the cartilaginous and bony sulcus angles could be used to differentiate between patients with or without trochlear dysplasia, and (3) whether the same cut-off of 145 degrees, originally used for radiographs, can be applied for the cartilaginous and bony sulcus ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…32 In human medicine, it is reported that there are differences between the SA measured for the articular cartilage surface and for the contour of subchondral bone. 33 Measuring methods which can reflect the articular cartilage surface, such as ultrasonography or magnetic resonance imaging, would enable more accurate evaluation of the femoral trochlear morphology. Computed tomographic examinations have more problems that they require sedation or general anaesthesia and are costly and time consuming in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…32 In human medicine, it is reported that there are differences between the SA measured for the articular cartilage surface and for the contour of subchondral bone. 33 Measuring methods which can reflect the articular cartilage surface, such as ultrasonography or magnetic resonance imaging, would enable more accurate evaluation of the femoral trochlear morphology. Computed tomographic examinations have more problems that they require sedation or general anaesthesia and are costly and time consuming in veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral instability is a common condition, affecting up to 49 people per 100,000. [1][2][3][4][5][6] One of the common anatomical factors associated with patellofemoral instability is that of an increased tibial tubercle-trochlear groove (TT-TG) distance. 4,7 The TT-TG distance is a measurement that quantifies the medial-lateral distance between the deepest part of the TG and the center of the patellar tendon insertion on the TT.…”
mentioning
confidence: 99%
“…13,36 On MRI scans, measurements utilizing bony versus cartilaginous landmarks are often performed interchangeably, despite evidence that they may differ in the evaluation of trochlear dysplasia. 33 Trochlear dysplasia has been more commonly reported in female patients, suggesting that increased anatomic risk factors may account for sex-specific differences in patellar instability. 4,15 Balcarek et al 4 reported in a study of 121 patients with patellar instability that female patients were more likely to have trochlear dysplasia and that a substantial interaction between sex and measurements of the sulcus angle and trochlear depth was identified.…”
Section: -In-5mentioning
confidence: 99%